Perkecambahan Dan Pertumbuhan Bibit Biwa (Eriobotrya japonica Lindl.) Akibat Perendaman Pada Urin Hewan Dan Pemotongan Benih - Lely Wahidah Nasution; Asil Barus; Lisa Mawarni; Rasiska Tarigan (Jurnal Agroekoteknologi, 2014)
This study aims to study the influence of animal urine and cutting of seed to support the seedlinggermination and growth of biwa. This research was conducted at Experiment Center of Fruit inBerastagi, Karo at April to July 2013. This research applies Randomized block design factorial,first factor: application of animal urine concentration in 25% and 50% by soaking during 15minutes and 30 minutes. Second factor: scarification techniques, P0=without cutting and P1=withcutting. The observation component consist of germination power, germination percentage,germination age, length of plant, number of leaves, leaf total area and root volume. The result ofresearch indicates that the soaking of biwa seed into animal urine and cutting has insignificantinfluence to the acceleration of seedling germination and growth. The treatment of soaking onanimal urine has a significant influence to the accelerate of seedling germination and growth onroot volume, age when germination, number of leave. The seed cutting of biwa has a significantinfluence to the accelerate of seedling germination and growth that indicated by root volume, andpercentage of germination. The best results showed that biwa seed was soaking in 50% cow urineconcentration for 30 minutes.Keywords: Eriobotrya japonica Lindl., germination, seed cutting, animal urine